Plan de negocio para diseñar una propuesta de implementacion de paneles solares para una mejor calidad de vida en la urbanización la Fortuna situada en la vereda de Sardinata municipio de Acacias Dpto. del Meta - Salinas Tovar, Dairo Junior (Universidad Antonio Nariño, 2022)
This business idea arises thanks to the La Fortuna urbanization located in the village of Sardinata, municipality of Acacias, Department of Meta; since this urbanization does not have a stable energy supply because the place where it is located is difficult to access, for this reason the start of the implementation of the solar panel system was concluded to improve the quality of life of the inhabitants of this village. Some of the advantages of solar energy are: it is renewable, it reduces electricity costs, it is silent, low maintenance and, above all, friendly to the environment. There are also some disadvantages of this system and among those are: that it is expensive in terms of its installation, intermittent since it depends on how much solar radiation it receives and that it occupies a lot of space, etc. By detailing the implementation of solar panels as an alternative solution to the problems caused by the constant power failures in the area. The basis of our product, on which the current photovoltaic systems to be used in our project for domiciliary residences are based, is the so-called photoelectric principle, through which the radiation of sunlight can be transformed into electrical energy.